Effects of jump training on physical fitness and athletic performance in endurance runners: A meta-analysis: Jump training in endurance runners. Issue 18 (17th September 2021) - Ramirez-Campillo, Rodrigo; Andrade, David C.; García-Pinillos, Felipe; Negra, Yassine; Boullosa, Daniel; Moran, Jason
ABSTRACT: This systematic review and meta-analysis aimed to assess the effects of jump training (JT) on measures of physical fitness and athletic performances in endurance runners. Controlled studies which involved healthy endurance runners, of any age and sex, were considered. A random-effects model was used to calculate effect sizes (ES; Hedge's g ). Means and standard deviations of outcomes were converted to ES with alongside 95% confidence intervals (95%CI). Twenty-one moderate-to-high quality studies were included in the meta-analysis, and these included 511 participants. The main analyses revealed a significant moderate improvement in time-trial performance (i.e. distances between 2.0 and 5.0 km; ES = 0.88), without enhancements in maximal oxygen consumption (VO2 max), velocity at VO2 max, velocity at submaximal lactate levels, heart rate at submaximal velocities, stride rate at submaximal velocities, stiffness, total body mass or maximal strength performance. However, significant small-to-moderate improvements were noted for jump performance, rate of force development, sprint performance, reactive strength, and running economy (ES = 0.36–0.73; p <  0.001 to 0.031; I 2  = 0.0% to 49.3%). JT is effective in improving physical fitness and athletic performance in endurance runners. Improvements in time-trial performance after JT may be mediated through improvements in force generating capabilities and running economy.